PELAKSANAAN RAPAT PERMUSYAWARATAN DALAM PERADILAN TATA USAHA NEGARA - I Putu Ristandi Pradana; Marwanto - (Kertha Negara : Journal Ilmu Hukum, 2013)
Consultative Meeting (the dismissal process) is a preliminary stage before theexamination principal dispute in the Administrative Court. Consultative Meeting isexamining the lawsuit that authorizes the chairman of the Court not to accept ordeclare the lawsuit is unfounded with a stipulation. This provision is found in Article 62of Act. No 5 of 1986. Within 14 days of the determination of the reading, do theresistance will be checked proceeding.